(untitled) (Baghdad Science Journal, 2024)
The prevalence of type 2 diabetes has doubled in recent years due to a defect in insulin production, which can develop to form diabetes complications that affect the kidneys, nerves, and eyes. As a result, early diagnosis and classification of Type II diabetes are critical to aiding physician assessments. Accordingly, the current study aimed to determine Retinol binding protein 4 (RBP4) levels in patients with T2DM and pre-DM as early predictors for disease cases. The current study included 138 subjects, divided into three groups, on the basis of FBG and HbA1c criteria, including (DM, 46 patients, pre-DM, 46 participants, and healthy subject,46 persons), when they enrolled in the National Diabetes Center- Al-Mustansiriya University. Enzyme-linked immunosorbent assays (ELISA) were used to detect the levels of Retinol Binding Protein 4 and Insulin, and spectrophotometric techniques were used to determine the levels of FBG and lipid profile. Retinol binding protein 4 results revealed significant differences (P≤0.0001) among the studied groups. Also, the insulin results showed significant differences (P≤0.0001) between the diabetic and control groups. The results of HOMA-IR showed significant differences (P≤0.0001). It also showed a lipid profile significant effect (P≤0.0022), (P≤0.0001), (P≤ 0.050) between the studied groups, except HDL that showed no significant difference(P≤.0.148). In conclusion, retinol-binding protein 4 can serve as an early indicator of T2DM, and this conclusion can be reinforced by the results of the ROC analysis, which indicated that Retinol binding protein 4 is an excellent indicator for diagnosis of the studied condition.